Benchmarks, sediment source and hydrodynamics of the 1755 Lisbon tsunami deposit at Boca do Rio Estuary - Font, Eric (2013)
Standardizing the signature of tsunami deposits has been pointed as a major limitation on the identification of paleo-tsunami deposits. This limitation majorly arises from the strongly source-dependent nature of these deposits, which in turn determines their composition and structure, and from the effect of the local morphology of the corresponding depositional environment. Here, we provide new high-resolution mineralogical, geochemical and paleontological data of the 1755 tsunami layer of Boca do Rio estuary (Algarve, Portugal) with the aim of unraveling the signatures of estuarine tsunami deposit and link them to sediment source.